ANTI-INFLAMMATORY ACTIVITIES OF AQUEOUS EXTRACT OF BERINGIN (FICUS BENJAMINA L.) AND KERSEN (MUNTINGIA CALABURA L.) LEAVES IN ALBINO RATS - Dominus Mbunga (JURNAL KATALISATOR, 2021)
Inflammation can increase the risk of various diseases. Currently, many drugs to treat inflammation have serious side effects. Ficus benjamina L. and Muntingia calabura L. have the potential to be safer and more efficient anti-inflammatory agents. Many pharmacological studies of the leaves of these plants have been carried out, but mostly did not use water extract even though traditionally the leaves were taken as infusion or decoction. This research aimed to prove the anti-inflammatory activities of aqueous extract of Ficus Benjamina L. and Muntingia Calabura L. leaves scientifically. Extraction was conducted by the Dekok method. Anti-inflammatory activities were performed based on the inhibition of edema on the paw of the rats, induced by carrageenan lambda 1 % intraplantarely. Results showed that all of the doses of the aqueous extract of Ficus benjamina L. and Muntingia calabura L. leaves had anti-inflammatory activities compared to the negative control (p<0.05). The highest anti-inflammatory activity on the aqueous extract of Ficus benjamina L. leaves was shown at the dose of 264 mg/kg bw with the edema volume percentage 39.71% compared to negative control group 70.12% and percentage of inflammation inhibition was 44.36%. On the aqueous extract of Muntingia calabura L. leaves, the highest anti-inflammatory activity was shown at the dose of 1284 mg/kg bw with the edema volume percentage 38.90%, and the percentage of inflammation inhibition was 46.83%.